An Act to Prevent the Carrying of Concealed Weapons, Aug. 10, 1871, reprinted in Laws of the District of Columbia: 1871-1872, Part II, 33 (1872) (Dist. of Col., An Act to Prevent the Carrying of Concealed Weapons, 1871, ch. XXV) - (:unkn) unknown (General Publisher, 1871)
Prohibited the carrying or having concealed “any deadly or dangerous weapons, such as daggers, air-guns, pistols, Bowie knives, dirk-knives, or dirks, razors, razor-blades, sword-canes, slungshots, or brass or other metal knuckles.” Punishable by forfeiture of the weapon and a fine of $20-50.
--
Keywords: CARRY